BAKING PROPERTIES OF FLOUR WINTER WHEAT GRAINS OF DIFFERENT VARIETIES DURING STORAGE - Завадская, Оксана (Modern engineering and innovative technologies, 2017)
The dynamics of technological and baking parameters of winter varieties of winter wheat four varieties during prolonged storage at different regimes was investigated. It was established that the best mode of storage was a controlled temperature regime, wh